Immunoregulatory functions of mature CD10+ and immature CD10– neutrophils in sepsis patients - Liu, Ming; Wang, Guan; Wang, Lin; Wang, Yuqi; Bian, Yuqing; Shi, Hang; Liu, Jie (Frontiers in Medicine, 2023)
Introduction Neutrophil plays a more and more important role in sepsis with paralysis of immunoregulation. Till now, there was no biomarker to identify and isolate the mature and immature neutrophils in sepsis patients. CD10 shows on mature neutrophils at the latest stages of its differentiation. Our study aimed to investigate whether CD10 was a valid biomarker for distinguishing immature and mature neutrophil subgroups under septic conditions and their immunoregulatory effects on lymphocytes. Methods Totally 80 healthy volunteers and 107 sepsis patients were recruited in this study. Fluorescence-conjugated anti-CD66b, and anti-CD10 monoclonal antibodies followed by incubation with specific anti-fluorochrome microbeads was used to isolate different subgroups of neutrophils. T cell apoptotic assays and T cell proliferation assays followed by flow cytometry analysis were used to evaluate the immunoregulatory effect of each subgroup of neutrophils. Results (1) The cytological morphology of CD10+ neutrophils was mature and that of CD10– neutrophils was immature in sepsis patients. (2) Mature CD10+ neutrophils inhibited the proliferation of T cell and immature CD10– neutrophils promoted the T cell proliferation. Conclusion (1) CD10 was a good biomarker to distinguish mature from immature neutrophils in sepsis patients. (2) Mature CD10+ and immature CD10– neutrophils displayed opposite immunoregulatory effects on T cells in sepsis patients.